The Cheese Biscuit Queen Tells All : Southern Recipes, Sweet Remembrances, and a Little Rambunctious Behavior - Greene, Mary Martha (Book collections on Project MUSE., 2021)
""I've been trying to decide whether to cook and then read or read and then cook, because either way is tempting. Having eaten my way through an entire recipe of cheese biscuits I can attest to the recipes. Just be careful you don't get so engrossed in the stories you let something burn." --Nathalie Dupree Mary Martha Greene's Aunt Mimi was known throughout South Carolina and beyond for her cheese biscuits. The living image of QEII, Aunt Mimi made the light and crisp biscuits for sixty years, and when she passed away, it was all Mary could do but learn the recipe and take up the mantel of Cheese Biscuit Queen. In The Cheese Biscuit Queen Tells All, Greene shares more than 100 recipes and touching and hilarious stories from her ever-so-Southern family and career in government relations. The book opens with the recipe (and family secrets) for the famous cheese biscuits and includes classic and modern dishes like Country Ham Scones, Frogmore Stew Dip, Shrimp and Corn Pie, and Lemon Pound Cake. With new ideas for the consummate entertainer, helpful tips for less experienced cooks, and stories to make even the grumpiest senator laugh, the Cheese Biscuit Queen has a place in every kitchen"--